The Slaughter of the Bison and Reversal of Fortunes on the Great Plains - Donn. L. Feir; Rob Gillezeau; Maggie E. C. Jones (Institute of Labor Economics (IZA), 2022)
In the late nineteenth century, the North American bison was brought to the brink of extinction in just over a decade. We demonstrate that the loss of the bison had immediate, negative consequences for the Native Americans who relied on them and ultimately resulted in a permanent reversal of fortunes. Once amongst the tallest people in the world, the generations of bison-reliant people born after the slaughter lost their entire height advantage. By the early twentieth century, child mortality was 16 percentage points higher and the probability of reporting an occupation 29.7 percentage points lower in bison nations compared to nations that were never reliant on the bison. Throughout the latter half of the twentieth century and into the present, income per capita has remained 28% lower, on average, for bison nations. This persistent gap cannot be explained by differences in agricultural productivity, self-governance, or application of the Dawes Act. We provide evidence that this historical shock altered the dynamic path of development for formerly bison-reliant nations. We demonstrate that limited access to credit constrained the ability of bison nations to adjust through respecialization and migration.
Keywords: I15; J15; N31; N32; O10; 330; North American Bison; Buffalo; extinction; economic history; Native Americans; indigenous; income shock; intergenerational mobility